Constraints on the origin of south indian magnesite deposits - PRASANNAKUMAR, V. (Boletim Paranaense de Geociências, 2002)
Most of the magnesite deposits in South India are confined to the southern part of the Dharwar craton and are associated with the ultramafics emplaced into the older supracrustal rocks. The major mineralisation is located in a shear zone that separates the Early Proterozoic and Pan-African granulites. The timing of mineralisation and the source of carbon for the various magnesite deposits of South India are points of debate. Temporal relations of deformation, metamorphism, incipient charnockitisation and mineralisation in the shear zone have been analysed. On the basis of the CO 2 influx, which favoured the formation of incipient charnockites, it is presumed that a juvenile CO 2 rich solution might have significantly contributed to the source of carbon for magnesite mineralisation. The present study attributes the timing of magnesite mineralisation to Pan-African time.